Influence of Private Institutions’ Participation on Access to University Education in South Western Nigeria (1999-2008) (2012)
The issue of access to university education has been a great concern to the government, scholars, university institutions and the society at large. Studies have shown that public universities have been admitting less than twenty percent of applicants owing to low funding, inadequate infrastructure, poor quality and limited space available for applicants. This has prompted the participation of private institutions in the provision of university education. However, with over a decade of private participation in university education provision, there have not been many empirical studies on their influence on access to university education. Besides, there has also been a dearth of literature on the paradigm shift in this new trend in university education provision in Nigeria. This study, therefore, examined private institutions‟ perception of the influence of their participation on access to university education in Southwestern Nigeria between 1999-2008. The descriptive survey research design was adopted. One thousand and twenty respondents comprising 30 principal management staff, 30 senior registry staff, 60 senior academic staff and 600 students from six private universities were selected using stratified and random sampling techniques. Private Institutions Participation Scale (r = 0.82) and University Access Questionnaire (r = 0.85) were used for data collection. These were complemented with six sessions of key Informant Interviews (KII) and secondary data including bulletins, official gazettes and information handbook from the six universities. Four hypotheses were tested at 0.05 level of significance. Data were analysed using frequencies, percentages, Pearson‟s Product Moment Correlation and Multiple regression, while qualitative data were content analysed. Private institutions‟ participation significantly influenced access to university education (F(6,1013) = 158.99; p<0.05) and contributed 48.50% to the variance of access to university education. The relative contributions of the components of private institutions‟ participation were as follows: flexible tuition payment ( = 0.852, p<0.05), flexible admission requirement ( = 0.625, p<0.05), attrition rate ( = 0.503, p<0.05) diverse courses ( = 0.0396, p<0.05), infrastructure ( = 0.243, p<0.05) and uninterrupted academic programmes ( = 0.054, 27. p<0.05). There was a significant increase in the ratio of access to private universities from 1.16 in 1999 to 14.22 in 2008. Also, the yearly, average enrolment created by private universities between 1999 and 2008 increased significantly by 705.5%. Private institutions‟ participation also correlated with quality assurance in university education (r = 0.46). The KII results showed that despite the remarkable contributions to access to university education, access opportunities are still elusive to thousands of applicants due to limited admission capacity and high tuition fees in the institutions. Private institutions‟ participation improved access to university education in Southwestern Nigeria. Operators of private universities should attempt to increase access to university education by providing more infrastructure, improving the flexibility of tuition payment, and admission requirements without compromising quality. Further studies could explore comparison of access creation to university education in public and private universities in other parts of the country.